Studi Eksplorasi Dampak Work From Home Terhadap Kinerja Karyawan Di Masa Pandemi Covid-19 Pada Bumn Di Wilayah Denpasar - Putu Pradiva Putra Salain; Made Santana Putra Adiyadnya; Putu Agus Eka Rismawan (Universitas Mahendradatta Denpasar, 2020)
The purpose of this study was to identify and obtain information regarding the strengths and weaknesses of the concept of working from home during the Covid-19 pandemic. This study uses an exploratory case study method and its research approach uses a qualitative method used to obtain information on the strengths and weaknesses of the concept of working from home during the Covid-19 pandemic. In this study the number of respondents used was 10 employees of state-owned enterprises (BUMN) in the Denpasar area. For purposes of confidentiality, respondents are given the initials K1 through K10 with semi-structured interview techniques and a list of questions compiled and developed based on the related literature. The results of this study are the concept of work from home provides advantages and disadvantages for employees. The advantage referred to is that employees can save on transportation costs so that this is used to divert transportation expenses to meet household needs and to prevent the spread of Covid-19. While the lack of work from home in this case both in terms of internet costs, home atmosphere distruction and decreased levels of employee motivation in completing work.